The significance of radiation-induced chromosome abnormalities in radiological protection - Dolphin, G. W. (1974)
A brief review is given of the production and analysis of chromosome aberrations induced by ionizing radiation. The various tissues in which it is possible to demonstrate aberrations are noted and particular emphasis is laid on the culture of peripheral blood lymphocytes. Some examples of recent applications of the technique are described. These are in the determination of suspected overdoses to radiation workers, in estimating doses to radiotherapy patients, and investigating the depth/biological profile for a negative π meson beam.